Not yet another negative trial-ReACTing on recent glioblastoma trials - Wick, Wolfgang; Wagener, Jan Robin (Clinical cancer research, 2020)
The present ReACT trial provides data from a small randomized controlled vaccination trial that in addition to other recent immunotherapy trials in glioblastoma allows sketching a rational, advanced trial design for the development of (immune) therapies in glioblastoma elaborating on but not restricting to biological monitoring and endpoints.See related article by Reardon et al., p. 1586
Gesehen am 20.04.2020